Implementasi Data Mining Menggunakan Algoritma Apriori Dalam Menentukan Persediaan Barang - Yulia Ananda Br. Sembiring; Emy Alfiani Sembiring (ADA Research Center, 2023)
The needs of people in the lower middle and upper middle economic categories. However, small shops often experience problems in managing the inventory of goods or materials needed by customers. This can lead to a lack of goods that customers want, and ultimately disappoint them. Therefore, inventory control is very important in maintaining customer satisfaction and business continuity for small shops. To help overcome this problem, research can be carried out using the Apriori algorithm. This algorithm can help identify the most sold products, so that small shops can organize optimal inventory. In this way, small shops can meet customer needs effectively and efficiently, and avoid stockouts that can disrupt customer satisfaction. In research, several variables are used to collect data, such as transaction date, product name, and number of sales/purchases. This data can then be analyzed using the Apriori algorithm, so that the most sold products can be identified and used as a basis for optimal inventory management.